68‐1: Investigation on Defocusing‐Induced Accommodation Shift in Microlens Array‐Based Near‐Eye Light Field Displays. Issue 1 (25th September 2020) - Qin, Zong; Wu, Jui-Yi; Chou, Ping-Yen; Xie, Jing; Huang, Cheng-Ting; Chen, Jang-Lin; Shieh, Han-Ping D.; Huang, Yi-Pai
Abstract : The accommodation response in a microlens array‐based near‐eye light field display is found to considerably shift towards the central depth plane but not at the reconstructed depth plane due to defocusing of the lens array. The shifts are characterized and can be fully addressed by compensating in a binocular system.